2019
DOI: 10.1111/ele.13440
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural intensification drives changes in hybrid network robustness by modifying network structure

Abstract: Within ecological communities, species engage in myriad interaction types, yet empirical examples of hybrid species interaction networks composed of multiple types of interactions are still scarce. A key knowledge gap is understanding how the structure and stability of such hybrid networks are affected by anthropogenic disturbance. Using 15,169 interaction observations, we constructed 16 hybrid herbivore‐plant‐pollinator networks along an agricultural intensification gradient to explore changes in network stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 98 publications
2
57
1
Order By: Relevance
“…Species interaction networks can also reveal how communities change and which species are winners and losers when native forest is converted to agriculture. For instance, specialist species (those with few interaction partners or highly selective interaction partner choice) are typically more vulnerable to environmental change, and thus less common in human-made habitats [9,21]. Greater interaction partner specificity indicates greater niche partitioning within a community, meaning that specialized species may reduce interspecific competition, allowing for greater biodiversity maintenance [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Species interaction networks can also reveal how communities change and which species are winners and losers when native forest is converted to agriculture. For instance, specialist species (those with few interaction partners or highly selective interaction partner choice) are typically more vulnerable to environmental change, and thus less common in human-made habitats [9,21]. Greater interaction partner specificity indicates greater niche partitioning within a community, meaning that specialized species may reduce interspecific competition, allowing for greater biodiversity maintenance [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The methods for data collection were originally published in Morrison et al (2019) but we briefly summarize them here. The study took place in Santa Cruz and Monterey counties, California, U.S.A. We selected 16, 4 ha sites that fell along a gradient of agricultural intensification.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we use plant-pollinator interaction networks from 16 sites along a gradient of agricultural intensification (Morrison, Brosi, & Dirzo, 2019) to explore whether linkage rules of plant-pollinator interactions change with disturbance context. We chose to focus on a gradient of agricultural intensification as it is the dominant driver of global change (IPBES, 2019) yet it has considerable potential for supporting biodiversity and ecosystem services (Kremen & Merenlender, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among all stressors, the effects of rising temperature and biological invasions received most attention. Temperature directly affects organisms' metabolic rate, for example by favouring C 4 plants (Zavaleta et al, 2003), with likely implications for entire food webs (Moya-Laraño et al, 2012). Field experiments have shown that different trophic groups will likely respond differently to increased temperature, yet consistently leading to a simplification of the food web either in agricultural fields (Derocles et al, 2018), grasslands (de Sassi et al, 2012) or in streams (O'Gorman et al, 2012).…”
Section: Patternsmentioning
confidence: 99%
“…Pollination networks are also affected by the arrival of super-generalist invasive species, although changes on overall food web structure have been hard to identify (Traveset et al, 2015;Vilà et al, 2009). Other stressors, such as agriculture intensification and habitat fragmentation have also been shown to simplify plant-animal interactions, usually by concentrating energy flow along fewer pathways in intensively managed landscapes (Albrecht et al, 2007;Morrison et al, 2020;Tylianakis et al, 2008Tylianakis et al, , 2007. Urbanization is also known to affect natural food webs (Faeth et al, 2005); however generalization on the magnitude or direction of such effects is still not really possible due to the difficulty of disentangling the effects from multiple associated drivers, the variability in the concept of urbanization, and paucity of studies.…”
Section: Patternsmentioning
confidence: 99%